ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN BERBASIS MASALAH MATA PELAJARAN IPA DI SD - Rianingsih Putri Lassari; Linda Zakiah; M. Syarif Sumantri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Critical thinking skills are the ability to solve problems and make decisions when facing a problem. Critical thinking skills can consist of the ability to analyze, interpret, evaluate, summarize, and synthesize various information to prevent negative impacts from occurring. The purpose of this study was to describe and identify students' critical thinking skills. The method used in this research is descriptive quantitative method. Data were collected through survey techniques in the form of questionnaires using test instruments. The results of this study are the average level of students' critical thinking skills at 54.75%. One of the efforts to improve students' critical thinking skills is to apply a problem-based learning model. This is in line with the purpose of science learning, which is to develop student’s' thinking skills in the learning process so that they can apply natural science concepts in their daily activities.